2008
DOI: 10.1055/s-2008-1038386
|View full text |Cite
|
Sign up to set email alerts
|

Management of Poststernotomy Mediastinitis: Experience and Results of Different Therapy Modalities

Abstract: As a primary treatment for PM two treatment modalities are currently in use: primary reclosure coupled with a double-tube suction/irrigation system versus V. A. C.(R) therapy. Since prospective randomized studies have not yet been performed, controlled clinical trials comparing both treatment modalities are pivotal to define the evidence for patients presenting with PM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 19 publications
1
31
0
3
Order By: Relevance
“…The frequency of this complication varies globally partly due to definitions used, however some centres have reported rates between 0.2% and 8% [5] and others ranging between 0.25% and 4% [6] of cardiac surgeries. In Australia, approximately 23,000 cardiac surgical procedures are conducted annually [7].…”
Section: P Ost Sternotomy Deep Sternal Wound Infection (Dswi)mentioning
confidence: 99%
“…The frequency of this complication varies globally partly due to definitions used, however some centres have reported rates between 0.2% and 8% [5] and others ranging between 0.25% and 4% [6] of cardiac surgeries. In Australia, approximately 23,000 cardiac surgical procedures are conducted annually [7].…”
Section: P Ost Sternotomy Deep Sternal Wound Infection (Dswi)mentioning
confidence: 99%
“…One of the life-threatening complications that occurs in patients following cardiovascular surgery through median sternotomy is deep sternal wound infection (DSWI). The incidence of DSWI that has been reported ranges from 0.2% to 8% (2,3). However, the mortality varies from 8% to 45%.…”
Section: Introductionmentioning
confidence: 99%
“…However, a consensus as to best treatment for mediastinal infection has yet to be established. For example, Schimmer et al recently surveyed 79 cardiac surgery programs in Germany to query DSWI management strategies [71]. They found that approximately 1/3 of the centers preferentially used NPT for controlling mediastinal contamination, while another 1/3 use closed chest irrigation, and another 1/3 combine management approaches [71].…”
Section: Treatment Of Dswimentioning
confidence: 99%
“…For example, Schimmer et al recently surveyed 79 cardiac surgery programs in Germany to query DSWI management strategies [71]. They found that approximately 1/3 of the centers preferentially used NPT for controlling mediastinal contamination, while another 1/3 use closed chest irrigation, and another 1/3 combine management approaches [71]. Other groups continue to advocate more aggressive surgical therapy in addressing infected sternal wounds [7,72].…”
Section: Treatment Of Dswimentioning
confidence: 99%